Предмет: Алгебра,
автор: Ezioa11
Y=-5x^2+1
.
Найти:y(2) y(0) y(-3)
Ответы
Автор ответа:
0
у = -5х^2 + 1
у(2) = -5 * 2^2 + 1 = -5 * 4 + 1 = -19
у(0) = -5 * 0^2 + 1 = 0 + 1 = 1
у(-3) = -5 * 3^2 + 1 = -45 + 1 = -44
у(2) = -5 * 2^2 + 1 = -5 * 4 + 1 = -19
у(0) = -5 * 0^2 + 1 = 0 + 1 = 1
у(-3) = -5 * 3^2 + 1 = -45 + 1 = -44
Похожие вопросы
Предмет: История,
автор: hron500
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: agarich87katya
Предмет: Математика,
автор: seremelnik
Предмет: Математика,
автор: ekaterinaok2000